2017
DOI: 10.1007/s00256-017-2697-3
|View full text |Cite
|
Sign up to set email alerts
|

Glomangiomatosis: a case report

Abstract: Glomangiomatosis is a benign vascular variant of a glomus tumor. The lesion represents only 5% of glomus tumors with unusual or atypical features and even fewer glomus tumors with typical features. The lesions are most commonly located in the distal extremities and are multiple, deep, extensive, and often pain producing. They develop from small arteriovenous anastamoses and are most often identified in young adults. The lesions may recur. We present a case of a 33-year-old male who presented clinically with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Skeletal muscle infiltration was observed in 5 cases, and extensive nerve and peripheral invasion was seen in 1 case. However, some authors suggest that the glomus cells and angiomatosis components in glomus hemangioma, often accompanied by adipose tissue, are a sign of mesenchymal proliferation and not simple glomus cell proliferation[ 3 , 10 ]. Further study is necessary to determine whether adipose is one of its components or whether it infiltrates into the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skeletal muscle infiltration was observed in 5 cases, and extensive nerve and peripheral invasion was seen in 1 case. However, some authors suggest that the glomus cells and angiomatosis components in glomus hemangioma, often accompanied by adipose tissue, are a sign of mesenchymal proliferation and not simple glomus cell proliferation[ 3 , 10 ]. Further study is necessary to determine whether adipose is one of its components or whether it infiltrates into the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was positive for SMA and negative for CD34. Fitzhugh et al [ 10 ] reported a 33-year-old man with a mass on the distal right calf. Immunohistochemistry showed that the tumor cells were diffusely and strongly positive for SMA, and the vascular components were strongly positive for CD31 and CD34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are a subtype of atypical glomus tumor as it falls outside the normal clinical and/or histologic spectrum of typical glomus tumors. It has an estimated incidence if 2 in 1,000,000 and accounts for 2%-3% of glomus tumors in adults [ [3] , [4] , [5] ]. Both typical glomus tumors and glomangiomas are painful and typically occur in the extremities [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first reported case of a glomangioma involving the distal tibiofibular syndesmosis. Glomangiomas are typically seen as soft tissue masses that are homogenously T1 hypo-to–isointense, heterogeneously T2 hyperintense and demonstrate post-contrast enhancement [ 3 , 4 , 8 ]. This case demonstrates non-fat suppressing T1 hyperintensity ( Fig.…”
Section: Discussionmentioning
confidence: 99%